Non-conventional monetary policies: QE and the DSGE literature - Evren Caglar; Jagjit S. Chadha; Jack Meaning; James Warren; Alex Waters (University of Kent, School of Economics, 2011)
At the zero lower bound, the scale and scope of non-conventional monetary policies have become the key decision variables for monetary policy makers. In the UK, quantitative easing has involved the creation of a fund to purchase medium term dated government bonds with borrowed central bank reserves and so has increased the liquidity of the non-bank financial sector and temporarily eased the budget constraint of HMT. Some of these reserves have been used to increase the extent of capital held by banks and there have also been direct injections of capital into the banking system. We assess some of the issues arising from the three policies by using three separate DSGE models, which take seriously the role of financial frictions. We find that it is possible to correct the effects of a lower zero bound in DSGE models, by (i) offsetting the liquidity premium embedded in long term bonds and/or (ii) adopting countercyclical subsidies to bank capital able and/or (iii) the creation of central bank reserves that reduce the costs of loan supply. But the correct quantitative response and ongoing interaction with standard monetary policy remains an open question.
Keywords: E31; E40; E51; 330; zero bound; open-market operations; quantitative easing